Geochemical analyses of recent sediments from Lake Morzycko against selected physiographic parameters of the Słubia River catchment (Western Poland) - Adamek, Anna; Mareczka, Paulina; Jucha, Witold; Musielak, Stanisław; Okupny, Daniel (Acta Geographica Lodziensia, 2021)
This paper presents the results of a study on the content of lithogeochemical components (organic matter, Na, K, Mg, Ca, Mn, Fe, Cu and Zn) and grain-size composition of mineral matter in the bottom sediments of Morzycko Lake (Myślibórz Lakeland, NW Poland). This lake is large (342.7 ha) and deep (69 m). The catchment has a typical forested character (mainly in the middle part of the Słubia River valley) with agricultural area (mainly in the upland areas north of the lake). The diversity of concentrations of metals was analysed based on 44 samples from 22 representative sites, including surface sediments and sediments from 5 cm below the current lake bed. The results showed that the chemical composition and granulometry of bottom sediments depends on contemporary morphogenetic processes in the catchment of the Słubia River. Geochemical and grain-size indices varied due to changes in biological productivity, intensity of weathering of postglacial material making up the catchment, and potential for migration of metals to the lake with surface or underground runoff. An important aspect in assessing the degree of enrichment of the sediments in trace elements is the location of shallow parts of the lake near the tourist districts of Moryń.